PENGARUH NML CAPITAL TERHADAP KEBIJAKAN GHANA MENYITA KAPAL ARA LIBERTAD MILIK ARGENTINA TAHUN 2012 - Fahrefi, Adib; Fachri, Yuli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study analyzes the foreclosure dispute problem Ship conducted by Ghana who seized the ship ARA Libertad belong to Argentina in 2012, the seizure of the ship in the background backs by the influence made by NML Capital, which is a Multi National Corporation (MNC) which is based in the United States. Argentina ever build cooperative relationships Fiscal Agency Agreement (FAA) with NML Capital in 1994 experienced a problem on debt payments, Argentina did not pay their debts to the NML Capital due to several things, which led to NML Capital demanding Argentina to the level of appeal in the Supreme Court of England regarding payment debt, the decision of the appeal at the Supreme Court level, NML Capital gain verdict that NML Capital reserves the right to freeze the assets of Argentina that is outside the countryAuthors collected data from books, encyclopedias, journals, media and website in analyzing the NML Capital Influence in policies Ghana seized the ship ARA Libertad. This study used a liberal paradigm. The theory used is the state and the Multinationals of Robert Gilpin in the book Global Political Economy: Understanding the International Economic Order. This study shows how a Multi-National Corporation (MNC) can affect the measures taken State and cause of action-reaction between the State, Ghana interest in this case the seized ship ARA Libertad is considered as an attempt to make a profit to NML Capital, and the arrest of the vessel Policy this affects the relationship Ghana and Argentina.